2019
DOI: 10.1007/s40615-018-00557-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Prevalence, Treatment, and Related Behaviors Among Asian Americans: An Examination by Method of Measurement and Disaggregated Subgroups

Abstract: Background: Data on hypertension among Asian Americans is lacking and often aggregated, which can mask important ethnic differences. This study aims to provide a comprehensive view of hypertension and hypertension related behaviors, including hypertension treatment, management, and information seeking, among Chinese, Korean, and Vietnamese Americans. Methods: Data were collected from 600 foreign-born Asian Americans (201 Chinese, 198 Korean, and 201 Vietnamese participants) in the Washington-Baltimore metropol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…This is compared to data from another study that found among Asian Americans in Los Angeles County, 32.9% ages 50–64 and 59.6% ages 65 + had hypertension [ 42 ]. Although the prevalence of hypertension in our sample seems higher than a previous age-adjusted estimate of hypertension of 27.5% among Chinese, Korean, and Vietnamese adult participants 18 years-old and older in the Washington-Baltimore Metropolitan Area, the prevalence of hypertension in our study seems similar to other research on middle-aged and older Asian Americans [ 7 , 43 ].…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…This is compared to data from another study that found among Asian Americans in Los Angeles County, 32.9% ages 50–64 and 59.6% ages 65 + had hypertension [ 42 ]. Although the prevalence of hypertension in our sample seems higher than a previous age-adjusted estimate of hypertension of 27.5% among Chinese, Korean, and Vietnamese adult participants 18 years-old and older in the Washington-Baltimore Metropolitan Area, the prevalence of hypertension in our study seems similar to other research on middle-aged and older Asian Americans [ 7 , 43 ].…”
Section: Discussionsupporting
confidence: 60%
“…These findings coincide with other studies finding that older Asian Americans and men are more likely to have hypertension [ 6 , 42 , 46 ]. Further, studies have found Korean Americans have higher prevalence of hypertension than Chinese Americans [ 7 , 47 ]. Our finding that being married/cohabitating was associated with higher likelihood of diagnosed hypertension contradicts prior studies of this topic [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations